Centrality and pseudorapidity dependence of the transverse energy density in pPb collisions at √sNN=5.02 TeV; Physical Review C; Vol. 100, iss. 2 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Babaev A. A. Anton Anatoljevich (2019, 2019)
Title screen